2020
DOI: 10.1007/s11229-020-02595-2
|View full text |Cite
|
Sign up to set email alerts
|

Formal models of source reliability

Abstract: The paper introduces, compares and contrasts formal models of source reliability proposed in the epistemology literature, in particular the prominent models of Bovens and Hartmann (Bayesian epistemology, Oxford University Press, Oxford, 2003) and Olsson (Episteme 8(02):127-143, 2011). All are Bayesian models seeking to provide normative guidance, yet they differ subtly in assumptions and resulting behavior. Models are evaluated both on conceptual grounds and through simulations, and the relationship between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Several important aspects of the belief-updating process were omitted in this study. One such factor is the credibility of the source presenting the evidence (Chung et al, 2008; Merdes et al, 2020). Future studies could explore how an information source affects the incorporation of evidence into one’s belief system and how this impact might interact with ideology.…”
Section: Discussionmentioning
confidence: 99%
“…Several important aspects of the belief-updating process were omitted in this study. One such factor is the credibility of the source presenting the evidence (Chung et al, 2008; Merdes et al, 2020). Future studies could explore how an information source affects the incorporation of evidence into one’s belief system and how this impact might interact with ideology.…”
Section: Discussionmentioning
confidence: 99%
“…In such a model, an agent is updating a joint assignment of degrees of belief for both hypotheses and source reliabilities. Several different Bayesian models of source reliability have been developed in the literature (Olsson 2013;Bovens and Hartmann 2003;Merdes et al 2020). We focus here on the type of model presented by Bovens and Hartmann (2003).…”
Section: Source Reliability Modelsmentioning
confidence: 99%
“…Their model has found applications in the philosophy of science concerning the epistemological Variety of Evidence Thesis (Bovens and Hartmann 2002;Claveau 2013;Claveau and Grenier 2019;Stegenga and Menon 2017;Landes 2020b, a), which states that varied evidence for a hypothesis confirms it more strongly than less varied evidence, ceteris paribus. Furthermore, it has been employed in Hahn et al (2016) for modelling social debates of findings in climate science, the philosophy of economics Casini and Landes (2020) and (the philosophy of) medicine (Abdin et al 2019;Landes et al 2018;De Pretis et al 2019;.…”
Section: Background and Motivationmentioning
confidence: 99%
“…But do we perceive of unreliable sources as providing no relevant information towards hypothesis confirmation? Collins et al (2015; found that human subjects tend to favour the construal of unreliable sources put forward in Olsson (2011) over the approach of Bovens and Hartmann (2003), see also Merdes et al (2021). In this approach, unreliable sources are construed as sources which always lie, i.e., the testimony of an unreliable agent is the exact opposite of what she thinks.…”
Section: Background and Motivationmentioning
confidence: 99%